Rancang Bangun Media Pembelajaran Algoritma Pemrograman Berbasis Android - Rizky Amalia; Saffana Assani’; Muhamad Afif Effindi; Etistika Yuni Wijaya; Nuru Aini (EDUTIC, 2023)
The digital age in the era of society 5.0 creates a technology that currently has significant developments that education needs to provide a new image of Indonesian education, namely by implementing a curriculum that is by the current curriculum. In teaching and learning activities, achieving an optimal result needs to pay attention to the existing learning principles. That is one way to attract the attention of students in the learning process. As well as with current technological advances making a physical book is something that is no longer attractive to today's students where at this time students are more and more often using smartphones. In teaching and learning activities carried out in schools today, informatics subjects still use physical books provided by the government. This causes students to not understand the concepts being taught and students will feel less interested in learning algorithms and programming. This study uses the Hannafin and Peck research method with the software used in product manufacture, namely ISpring Suite 10 and Website 2 APK Build. The results of this study are that the learning media product for Android-based programming algorithms using Blackbox Testing gives the result that the designed product works according to the expected results and is very suitable for use in students’ learning process.